Increased Serum Leptin Level Predicts Bone Mineral Density in Hemodialysis Patients - Chih-Hsien Wang; Yu-Hsien Lai; Yu-Li Lin; Chiu-Huang Kuo; Ru-Jiang Syu; Ming-Chun Chen; Bang-Gee Hsu (International Journal of Endocrinology)
Background. Leptin acts through the adipose-bone axis to regulate bone mineral density (BMD). This study evaluated the relationship between BMD and serum leptin levels in patients on hemodialysis. Methods. In this cross-sectional study including 98 hemodialysis patients, BMD was measured using dual energy X-ray absorptiometry of the lumbar vertebrae (L2–L4), and serum leptin levels were determined using an enzyme immunoassay. Results. There were 25 (25.5%), 13 (13.3%), and 60 (61.2%) patients with osteopenia, osteoporosis, and normal BMD, respectively. Advanced age P=0.017; decreased body mass index (BMI, P<0.001); body height P<0.001; prehemodialysis body weight (BW, P<0.001); post-hemodialysis BW P<0.001; waist circumference P<0.001; and triglyceride P=0.015, albumin P=0.004, and leptin levels P=0.017 were associated with lower lumbar T scores, whereas increased urea reduction rate (URR, P=0.004) and fractional clearance index for urea (Kt/V, P=0.004) were associated with lower lumbar T scores. The multivariable forward stepwise linear regression analysis with adjustment for sex; age; body height; prehemodialysis BW; BMI; waist circumference; logarithmically transformed triglycerides (log-triglycerides), albumin, creatinine, and leptin (log-leptin) levels; URR; and Kt/V indicated that high serum level of log-leptin (R2 change = 0.184; P<0.001), increased prehemodialysis BW (R2 change = 0.325; P=0.008), male sex (R2 change = 0.048; P=0.001), young age (R2 change = 0.044; P=0.012), and increased serum albumin level (R2 change = 0.017; P=0.044) were significantly and independently associated with lumbar BMD. Conclusions. Advanced age and female sex were associated with poor BMD, whereas increased BW, serum albumin, and leptin levels were positively associated with BMD in patients on hemodialysis.